Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
Let a = side length of a cube
Let S = surface area of a cube
Area of a square = a²
Since a cube has 6 square sides: S = 6a²
To make a the subject:
S = 6a²
Divide both sides by 6:
[tex]\sf \implies \dfrac{S}{6}=a^2[/tex]
Square root both sides:
[tex]\sf \implies a=\sqrt{\dfrac{S}{6}}[/tex]
(positive square root only as distance is positive)
-----------------------------------------------------------------------------------------------
[tex]\sf x=-3-\sqrt{2} \implies (x+[3+\sqrt{2}])=0[/tex]
[tex]\sf x=-3+\sqrt{2} \implies (x+[3-\sqrt{2}])=0[/tex]
Therefore,
[tex]\sf y=a(x+[3+\sqrt{2}]) (x+[3-\sqrt{2}])[/tex] for some constant a
Given the y-intercept is at (0, -5)
[tex]\sf \implies a(0+3+\sqrt{2}) (0+3-\sqrt{2})=-5[/tex]
[tex]\sf \implies a(3+\sqrt{2}) (3-\sqrt{2})=-5[/tex]
[tex]\sf \implies a(9-2)=-5[/tex]
[tex]\sf \implies 7a=-5[/tex]
[tex]\sf \implies a=-\dfrac57[/tex]
Substituting found value of a into the equation and simplifying:
[tex]\sf y=-\dfrac57(x+[3+\sqrt{2}]) (x+[3-\sqrt{2}])[/tex]
[tex]\sf \implies y=-\dfrac57(x^2+6x+7)[/tex]
[tex]\sf \implies y=-\dfrac57x^2-\dfrac{30}{7}x-5[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.